(3OjhGf MSjf GdWHGWHGFjs - (3MSjf Hf eMeO GdQVG Hf eMeO GdegOj HMQ GdYdhe GdWHGWHGFj,J (B1306 (3g` s ((3eMeO UGOb Hf GdMSf Hf EHQGgje Hf UGMH GdOjhGf s)
(3ChdgG (B:s
(3hHYO(B: (3ajbhd cGfJ dj bUGFO YOjOI aCMHHJ Cf CLeY GdLejY aj OjhGf hbO QJHJgG JQJjH MQha GdgLGA s
(3BNQgG (B:s
(3hdSJ CfSi Pdc GdSerjO YG Yf MSf MeO hKfGA hoOYG ade jRd YeQ GdReGf OGFekG Yf cd eG jNTi eUhfkG SGdeG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B50s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B84 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs